2023
DOI: 10.3390/medicina59030472
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Diabetes Experienced More Serious and Protracted Sickness from the COVID-19 Infection: A Prospective Study

Abstract: Background and Objectives: In December 2019, a flu-like illness began in the Chinese city of Wuhan. This sickness mainly affected the lungs, ranging from a minor respiratory tract infection to a severe lung involvement that mimicked the symptoms of Severe Acute Respiratory Syndrome (SARS). The World Health Organization (WHO) labelled this sickness as a pandemic in March 2020, after it quickly spread throughout the world population. It became clear, as the illness progressed, that people with concomitant illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, blood glucose control and FPG level cannot be treated as independent predictors of clinical severity, and the relationship between blood glucose and COVID-19 requires further exploration. The CTSS can be used to evaluate and predict clinical classification and, in the meantime, offers some accuracy in predicting patient mortality [ 27 ], reminding us of the necessity of imaging examination in the diagnosis and treatment of patients with COVID-19. One Iranian study found no significant differences in clinical outcomes and chest CTSSs between patients with diabetes with good and poor blood glucose control [ 28 ], which is inconsistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, blood glucose control and FPG level cannot be treated as independent predictors of clinical severity, and the relationship between blood glucose and COVID-19 requires further exploration. The CTSS can be used to evaluate and predict clinical classification and, in the meantime, offers some accuracy in predicting patient mortality [ 27 ], reminding us of the necessity of imaging examination in the diagnosis and treatment of patients with COVID-19. One Iranian study found no significant differences in clinical outcomes and chest CTSSs between patients with diabetes with good and poor blood glucose control [ 28 ], which is inconsistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between COVID-19 infection and hyperglycaemia is bidirectional [ 12 ]. On the one hand, hyperglycaemia and diabetes mellitus have been shown to be risk factors for higher morbidity and mortality in patients with COVID-19 [ 13 , 14 ]. On the other hand, COVID-19 contributes to hyperglycaemia (and even diabetes) due to impaired pancreatic beta-cell function and cytokine storm [ 15 ].…”
Section: Introductionmentioning
confidence: 99%